Peer feedback as a strategy to improve writing skills in B1 level EFL students. - Quintuña Barrera, Lady Viviana (2023)
Developing proficient writing skills in a foreign language poses challenges for learners of English as a Foreign Language (EFL), particularly at the B1 proficiency level. This qualitative study explores peer feedback's effectiveness in improving writing skills in B1-level EFL students, focusing on their experiences, perceptions, and attitudes towards the feedback process. Participants in this study are 4th-semester students enrolled in the Pedagogy of National and Foreign Languages career at University Statal Milagro. Through purposeful sampling, participants were selected based on their B1-level English proficiency, ensuring homogeneity in language skills and targeting their developmental stage in writing. The study employed a qualitative research design, incorporating semi-structured interviews as the primary data collection method. Based on these findings, the study concludes that peer feedback is an effective strategy for improving writing skills in B1-level EFL students. The results emphasize integrating peer feedback practices into language learning environments to foster collaborative and supportive learning communities. Furthermore, the study recommends conducting longitudinal research with more extensive and diverse samples to ascertain the long-term effects of peer feedback and to explore its applicability across different language proficiency levels.